CHRISTINA E. CRAWFORD - Spatial Revolution. Architecture and Planning in the Early Soviet Union - Garrido, Ginés (ZARCH, 2023)
Christina E. Crawford Spatial Revolution. Architecture and Planning in the Early Soviet Union Ithaca, Nueva York: Cornell University Press, 2022. 385 pp. Tapa dura. Idioma: inglés. 35,00 US ISBN. 978-1-5017-5919-2